Digital skills assessment in blended learning settings in mathematics and physics education programs - Maulidiya, Della; Putri, Desy Hanisa; Lestary, Ratnah (Universitas Negeri Yogyakarta, 2024)
Digitally savvy human resources are becoming more necessary. Through a survey, this research assesses students' digital skills after implementing blended learning. A total of 143 mathematics and physics teacher students provided their self-assessments of 25 indicators of digital skills. The findings show that around 50% of students can adapt to technology, and 61% rate it well for their creative ability in dealing with ideas. However, there is potential for improvement in problem-solving skills. In cultural awareness, more than 90% of students demonstrated respect for other cultures, although around 23% rated it sufficient for cultural understanding. Student ethics in using technology were high, with more than 85% stating they had good abilities. Assessments of core and contextual digital skills show a tendency for students to give higher ratings to core skills, but assessment variations are pretty significant. The mean scores and standard deviations for both skill categories indicate a level of variation that is noteworthy. This study provides in-depth insight into students' digital skills assessment, identifies potential areas for further development, and highlights the need for increased cultural awareness among students. This research recommends further investigation to determine the types of digital skills students gain from the wider use of the Internet and how well these skills fit the needs of the digital age.